Spreading the disease: Protest in times of pandemics - Martin Lange; Ole Monscheuer (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
This study analyzes the impact of COVID-19 deniers on the spread of COVID-19 in Germany. In a first step, we establish a link between regional proxies of COVID-19 deniers and infection rates. We then estimate the causal impact of large anti-lockdown protests on the spread of COVID-19 using an event study framework. Employing novel data on bus stops of travel companies specialized in driving protesters to these gatherings, and exploiting the timing of two large-scale demonstrations in November 2020, we find sizable increases in infection rates in protesters' origin regions after these demonstrations. Individual-level evidence supports the main results by documenting that COVID-19 deniers engage less in health protection behavior. Our results contribute to the debate about the public health costs of individual behavior that has detrimental externalities for the society.
Keywords: I18; I12; D62; P16; 330; COVID-19 deniers; protests; public health